Space law [electronic resource] : a treatise - Lyall, Francis; Larsen, Paul B. (Ashgat, 2009)
Space law is an area of International Law that has developed massively in the last fifty years and this book gathers together an extensive collection of the available literature on space law, providing an excellent source of discussion for both students